Mechanical-aerodynamic feedback in the process of sound generation - CZARNECKI, Stefan; CZECHOWICZ, Mieczysław; SOBOL, Teresa (Archives of Acoustics, 1980)
For many years phenomena of aerodynamic sound production have been known in the physical aspect, while a mathematical description of it is still in-sufficient. Therefore, investigations which have the increase of theoretical knowledge of this problem in view, have been performed. These investigations are concerned mainly with the interactions between aerodynamic and acoustic phenomena. However, in some cases of aerodynamic sound production, mechanical vibrations are of importance. The aim of this work is investigation of the set-up in which mechanical vibrations play an important part in aerodynamic sound production. An attempt is made to explain the mutual aero-vibroacoustie interactions by means of feedback systems. Laboratory tests were carried out in order to perform the preliminary verification.